A second endoscopic ultrasound with fine‐needle aspiration for cytology identifies high‐risk pancreatic cysts overlooked by current guidelines. Issue 1 (22nd September 2020) - Faias, Sandra; Pereira, Luisa; Fonseca, Ricardo; Chaves, Paula; Dias Pereira, António; Cravo, Marília
Abstract: Background: Endoscopic ultrasound with fine‐needle aspiration (EUS‐FNA) is recommended for diagnosis of pancreatic cystic lesions (PCLs). Its role in surveillance is unclear. Our goal was to determine if a second EUS‐FNA changes diagnosis or management of PCLs. Methods: A retrospective analysis of an EUS database, searching for EUS‐FNAs in PCLs from 2007 to 2017 was performed. Demographics, cyst characteristics, and FNA results were compared in patients under surveillance, performing a single or two consecutive EUS‐FNAs. Results: Of 203 PCLs referred for EUS‐FNA, surveillance was decided in 128 (63%). Data of 105 (82%) patients with a single EUS‐FNA were compared with 23 (18%) with two EUS‐FNAs during surveillance. Patients were younger in this latter group ( P = .055), whereas CEA levels were marginally higher ( P = .078) and a mass/nodule were more frequent ( P = .006). The mean time between EUS‐FNAs was 38 months (4.7‐118.8) for 18 patients maintaining surveillance vs 18 months (2.9‐56.9) in the four referred for surgery ( P = NS) after two EUS‐FNAs (two NETs, one IPMN‐HGD, and one MCN‐LG). A high correlation in CEA level between consecutive EUS‐FNAs ( r 2 = 0.945, P  < .01) was present, with a change of category observed (cut‐off level = 192 ng/mL) in two patients only. Of four patients with a second EUS‐FNA with conclusive cytology, two had NETs confirmed on resection. Conclusions: Repeating EUS‐FNA in surveillance of PCLs with clinical suspicion of malignancy increased neoplasm diagnoses, changing decision toward surgery in almost 20% of patients while excluding IPMNs with mucin nodules from unnecessary resections. A second EUS‐FNA for cytology appears justified in some PCLs, particularly for diagnosing NETs.